Long-Span Orthotropic Steel Deck Bridges of Turkey - Apaydin, Nurdan M.; Baş, Selçuk; Baş, Selçuk (Iop Publishing Ltd, 2018)
Long-span bridges are the key structures for transportation systems and they are considerably needed in Turkey since it is a transit country between Europe and Asia Continents. Besides, Turkey has many large reservoir dams, so these kinds of bridges are essential to provide transportation. Long-span orthotropic steel deck bridges are the main and the most important links in the transportation network of the country. This study presents the general features of the long-span orthotropic steel deck bridges in Turkey, namely The July 15 (the 1st Bosphorus) Martyrs Bridge, the Fatih Sultan Mehmet Bridge (the 2nd Bosphorus Bridge), the Yavuz Sultan Selim Bridge (the 3rd Bosphorus Bridge), the Osman Gazi (Izmit Bay) Bridge and the Canakkale 1915 (Dardanelles) Bridge. The importance behind the selection of long-span bridges in Turkey is explained and detailed information for recently ongoing project of the Canakkale 1915 Bridge is given. The outcomes from the current study are aimed to provide important vision for the construction of new long-span bridges in the world.
9th International Symposium on Steel Bridges -- SEP 10-11, 2018 -- Prague, CZECH REPUBLIC
Keywords: [No Keywords]